Identifikasi Pertumbuhan Urban Heat Island secara Spasial-Temporal di Kota Palangka Raya Menggunakan Penginderaan Jauh dan Sistem Informasi Geografis - Afrilyani Kontryana; Abdul Wahid Hasyim; Amin Setyo Leksono (Fakultas Teknik, 2021)
Developments in the city of Palangka Raya y giving different temperature between urban and sub-urban. Phenomenon that cities have warmer temperatures than sub-urban and rural areas called Urban Heat Island (UHI). This study aims to find out about the development of the UHI phenomenon in the city of Palangka Raya from 2000 to 2018 using remote sensing and geographical system. Based on the analysis of the TIR band landsat 7, in Kota Palangka Raya since 2000 has been UHI phenomenon, where high Land Surface Temperature (LST) was found dominantly in urban areas compared to sub-urban areas . In 2018, as Palangka Raya city had developed, based on the result of TIR band Landsat 8, the distribution of high LST not only found in the urban area, but in the sub-urban zone, especially at Menteng Urban Village and Panarung Urban Village. The development of UHI in Palangka Raya city over eighteen years (2000-2018) show in the sub-urban area experienced changes of UHIindex’s area more dynamic than the urban area. Urban development causing to conversion of vegetated land into impervious land, which greatly affects the energy balance. The increase in impervious areas causes more solar radiation that reaches the surfaces of the earth more absorbing and it is converted into sensible thermal energy which increases the surface temperature.